2020
DOI: 10.1167/iovs.61.4.23
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Particulates Affect Corneal Homeostasis and Immunity

Abstract: To determine the effects of airborne particulate matter (PM) <2.5 μm in vitro and on the normal and Pseudomonas aeruginosa (PA)-infected cornea. METHODS. An MTT viability assay tested the effects of PM 2.5 on mouse corneal epithelial cells (MCEC) and human corneal epithelial cells (HCET). MCEC were tested for reactive oxygen species using a 2 ,7-dichlorodihydrofluorescein assay; RT-PCR determined mRNA levels of inflammatory and oxidative stress markers in MCEC (HMGB1, toll-like receptor 2, IL-1β, CXCL2, GPX1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 68 publications
(100 reference statements)
2
8
0
Order By: Relevance
“…S4 ), which is markedly higher than the nation’s air quality standards (35 μg/m 3 ) according to the Environment Protection Agency. However, the PM 2.5 exposure concentrations used in this study are consistent with the common concentration range in the literature [ 50 , 53 , 54 ], which has been calculated based on the particle deposition rate [ 54 ]. For cell culture experiments, cytoxicity was observed with 500 μg/mL PM 2.5 [ 54 ] and 1 mg/mL PM 2.5 , which caused ocular surface damage in rats [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…S4 ), which is markedly higher than the nation’s air quality standards (35 μg/m 3 ) according to the Environment Protection Agency. However, the PM 2.5 exposure concentrations used in this study are consistent with the common concentration range in the literature [ 50 , 53 , 54 ], which has been calculated based on the particle deposition rate [ 54 ]. For cell culture experiments, cytoxicity was observed with 500 μg/mL PM 2.5 [ 54 ] and 1 mg/mL PM 2.5 , which caused ocular surface damage in rats [ 50 ].…”
Section: Discussionsupporting
confidence: 86%
“…Among the studies on the eye, Cui et al [66] suggested that PM causes a delay in corneal epithelium wound healing and ROS formation might play a critical role in this process. Recently, Somayajulu et al [67] established that PM 2.5 triggers ROS, which results in increased mRNA levels of oxidative stress and inflammation in mouse and human corneal epithelial cells. Although a few studies have suggested that PM triggers ROS generation in corneal and conjunctival epithelium, no studies on ROS and mitochondrial function upon PM have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…HCET cells (HCE-2 [50.B1], ATCC, Gaithersburg, MA, USA) were cultured in Keratinocyte-serum free medium (Gibco, Grand Island, NY, USA) with 5 ng/mL human recombinant EGF, 0.05 mg/mL bovine pituitary extract, 0.005 mg/mL insulin, and 500 ng/mL hydrocortisone as reported before [ 73 ]. HCEC (primary corneal epithelial cells, ATCC) were cultured in Keratinocyte-serum free medium (Gibco) with 5 ng/mL human recombinant EGF and 0.05 mg/mL bovine pituitary extract as per the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…An MTT 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (ThermoFisher Scientific, Grand Island, NY, USA) assay was used to test the effects of PM 10 on HCET viability in the presence and absence of SKQ1, per the manufacturer’s protocol and as reported before [ 73 ]. Briefly, 15,000 HCET cells were seeded in a 96-well plate, treated with increasing concentrations of PM 10 (0, 100 and 200 µg/mL) ± 50 nM SKQ1 and incubated for 24 h. At the end of the treatments, 5 mg/mL MTT reagent was added to each well and incubated at 37 °C for 4 h and the media was removed.…”
Section: Methodsmentioning
confidence: 99%